Characterization of nanoparticles prepared by acid hydrolysis of various starches - Kim, H. Y.; Lee, J. H.; Kim, J. Y.; Lim, W. J.; Lim, S. T.
Various starches of different AM contents and origins such as wx maize, normal maize, high AM maize, potato, and mungbean starches were hydrolyzed using a H2SO4 solution (3.16?M)at 40°C for 7 days, and the starch particles were isolated from the hydrolysates by centrifugation. The hydrolysis rates varied from 61.4 to 90.9 percent depending on the starch type. Unexpectedly, A-type starches were more resistant to the acid hydrolysis than B-type starches. XRD results revealed that the starch particles with B-crystalline type exhibited a decrease in peak intensity. In addition, in a DSC analysis, the crystals remaining in the B-type starch particles were readily disrupted in the water dispersion so that no melting endotherm appeared. Electron microscopy confirmed that the starch particles had round or oval shapes with diameters ranging from 40 to 70?nm, which possibly represented the starch blocklets in granules. The acid degraded mainly AM and long AP chains, resulting in increasing the proportion of short chains.
Keywords: ACID HYDROLYSIS; NANOPARTICLES; STARCH